Hukum Pernikahan dalam Islam: Analisis Perbandingan Konteks Menurut 4 Mazhab - Nurhasnah, Nurhasnah (Jurnal Pendidikan Islam, 2024)
Lately, there have been numerous marriage cases in Indonesia, including underage marriages, domestic violence, partner selection without proper knowledge of marriage. Therefore, it is important for all segments of society to be aware of the legal aspects of marriage for an individual. Hence, a study has been conducted with the theme "Marriage Law in Islam: Comparative Analysis According to 4 Mazhabs." The methodology used in this writing is a literature review. The results of this study reveal that there are fundamentally five categories of marriage laws in Islam: obligatory, recommended, prohibited, disliked, and permissible. Based on the contextual analysis by scholars from the four Mazhabs worldwide, they provide reasons for why marriage can be obligatory, recommended, prohibited, disliked, and even permissible. Specifically, the Shafi'i Mazhab presents four marriage laws: obligatory, recommended, disliked, and permissible, the Hanbali Mazhab also outlines four marriage laws: obligatory, recommended, prohibited, and permissible, while the Maliki and Hanafi Mazhabs present five marriage laws: obligatory, recommended, disliked, prohibited, and permissible.